Atypical traumatic bone cyst involving impacted lower third molar: report of case - Daniel Santiago VALE; Helena Bacha LOPES; Gileade Pereira FREITAS; Nilton Pires ARAUJO; Flavia Gabriela ROSA; Francisco NUNES JÚNIOR (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT The traumatic bone cyst is an uncommon nonneoplastic lesion of the jaws that is considered as a "pseudocyst" because of the lack of an epithelial lining. This lesion is particularly asymptomatic and, therefore, is diagnosed by routine dental radiographic examination as a unilocular radiolucency with scalloped borders, mainly in the posterior mandibular region. The exact etiopathogenesis of the lesion remains uncertain, though it is often associated with trauma. The objective of this paper is to report one case of atypical traumatic bone cyst involving impacted lower third molar, addressing its clinical and radiographic characteristics, differential diagnosis, treatment through surgical exploration and case follow-up.